2007
DOI: 10.1021/es0705745
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Intermediates of in Vivo Oxidation of 1,4-Dioxane by Monooxygenase-Containing Bacteria

Abstract: 1,4-dioxane is a probable human carcinogen and an emerging water contaminant. Monooxygenase-expressing bacteria have been shown to degrade dioxane via growth-supporting as well as cometabolic mechanisms. In this study, the intermediates of dioxane degradation by monooxygenase-expressing bacteria were determined by triple quadrupole-mass spectrometry and Fourier transform ion cyclotron resonance-mass spectrometry. The major intermediates were identified as 2-hydroxyethoxyacetic acid (HEAA), ethylene glycol, gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 30 publications
6
90
1
Order By: Relevance
“…Identification of candidate biomarkers was focused on monooxygenase and dehydrogenase genes based on earlier work describing the dioxane degradation pathway for monooxygenase-expressing bacteria (29,36) and expression of dehydrogenase genes in bacteria during utilization of monooxygenase-inducing substrates (37)(38)(39). To facilitate gene selection, an in silico analysis was performed to identify all annotated monooxygenase groups within CB1190 and its associated plasmids (35).…”
Section: Methodsmentioning
confidence: 99%
“…Identification of candidate biomarkers was focused on monooxygenase and dehydrogenase genes based on earlier work describing the dioxane degradation pathway for monooxygenase-expressing bacteria (29,36) and expression of dehydrogenase genes in bacteria during utilization of monooxygenase-inducing substrates (37)(38)(39). To facilitate gene selection, an in silico analysis was performed to identify all annotated monooxygenase groups within CB1190 and its associated plasmids (35).…”
Section: Methodsmentioning
confidence: 99%
“…strain ENV478 initially grown on THF (10). HEAA and 12 additional intermediates of dioxane degradation were subsequently detected for strain CB1190, including 2-hydroxy-1,4-dioxane, 2-hydroxyethoxyacetaldehyde, 1,4-dioxane-2-one, 1,3-dihydroxyethoxyacetic acid, 2-hydroxyethoxy-2-hydroxyacetic acid, glycoaldehyde, glyoxal, and formic acid (16). Even though a dioxane degradation pathway was proposed based on these detected intermediates (16), genes likely associated with several enzymatic steps in the pathway were only recently identified (17).…”
mentioning
confidence: 99%
“…HEAA and 12 additional intermediates of dioxane degradation were subsequently detected for strain CB1190, including 2-hydroxy-1,4-dioxane, 2-hydroxyethoxyacetaldehyde, 1,4-dioxane-2-one, 1,3-dihydroxyethoxyacetic acid, 2-hydroxyethoxy-2-hydroxyacetic acid, glycoaldehyde, glyoxal, and formic acid (16). Even though a dioxane degradation pathway was proposed based on these detected intermediates (16), genes likely associated with several enzymatic steps in the pathway were only recently identified (17). Transcriptional analyses showed that the putative THF monooxygenase (MO) gene cluster thmADBC in strain CB1190 was the only MO out of eight previously identified by genome sequencing (18) that was upregulated during growth on dioxane versus glycolate.…”
mentioning
confidence: 99%
“…P. dioxanivorans strain CB1190 (NCBI taxonomy ID 675635) was isolated from 1,4-dioxane-contaminated sludge and displays the rare ability to use 1,4-dioxane, an emerging groundwater contaminant, as a sole carbon and energy source (9,10,11,14). This strain can also grow on other ethers (e.g., 2-methyl-1,3-dioxolane and butyl methyl ether), alcohols, and benzene as the sole carbon and energy source, and it can grow autotrophically with CO 2 by using H 2 as the electron donor (9,14).…”
mentioning
confidence: 99%